Can 'legalization' of illegal forest activities reduce illegal logging?: lessons from East Kalimantan - Tacconi, L.; Obidzinski, K.; Smith, J.; Subarudi; Suramenggala, I. (2004)
Illegal activities are one of the most pressing problems facing the Indonesian forest sector today. The debate on illegal forest activities has focused primarily on legal and governance issues. Economic forces, however, are increasingly recognized as fundamental drivers of illegal forest activities. We ask the question whether the legalization of small logging concessions and their development can teach us anything about how to address the illegal logging problem. We find that legalization alone-when a legal timber concession is granted to a previously illegal operator-does not necessarily result in a significant reduction in illegal activities. When illegal activities are profitable, they can be expected to continue. Changing the regulatory framework to increase monitoring and enforcement can affect the profitability of these illegal activities. By changing the underlying economic incentives for logging, such interventions hold greater promise of success. In the medium to long term, however, legalization may help reduce illegal logging when it entrusts local people with ownership and control of forest resources and maintains a monitoring role for government agencies.